Protocol for the recombinant expression and purification of the LSAM domain of human legumain in E. coli - Sven O. Dahms; Alexander C. Wieland; Hans Brandstetter; Elfriede Dall (STAR Protocols)
Summary: Expressing disulfide-rich proteins in E. coli is challenging due to incorrect bond formation. Here, we present a protocol for expressing the PC1pro-LSAM fusion protein in E. coli using the PC1 prodomain as a fusion tag and the legumain stabilization and activity modulation (LSAM) domain as a proof-of-concept target that was purified. We describe steps for characterizing the protein’s structural integrity through multiple biochemical and biophysical parameters like molecular weight, melting temperature, and secondary structure content. This protocol enables efficient expression of disulfide-containing proteins previously incompatible with bacterial systems. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.